Inovasi Pelayanan Publik Melalui Aplikasi Berbasis Website Link and Match ASSIK (Arek Suroboyo Siap Kerjo) di Dinas Perindustrian dan Tenaga Kerja Kota Surabaya - Novanti, Hany Dwi; Meirinawati, Meirinawati (Universitas Negeri Surabaya, 2024)
This research aims to provide a description and analysis of the innovation of the ASSIK link and match website application at the Surabaya City Industry and Labor Office. The type of research used in this study is descriptive with a qualitative approach. This research focuses on measuring public service innovation, including governance and innovation, innovation idea sources, innovation culture, capabilities and tools, goals, outcomes, drivers, and barriers, and the collection of innovation data for single innovations. Data collection techniques used in research include interviews, documentation, and observations. Research results show that from several indicators of innovation success, this ASSIK application has been implemented well, but there are still several problems regarding ISO-certified management systems and application procedural technical constraints, as evidenced by community complaints about bug and error systems, slightly less efficient features, and less attractive application design. However, not a few people in Surabaya have been helped and made easier by the innovation of this ASIK application, so that they can get a job through the ASIK application. Between 2022 and 2023, the city's TPT decline was 0.86%, which showed a decrease in the Surabaya City TPT rate, which partly came from the ASSIK application program and contributed to reducing the number of unemployed people in Surabaya. Although the TPT figures have not shown a significant decline, this has shown a good contribution and will continue to be implemented until the city of Surabaya becomes unemployment-free. Keywords: Innovation, ASSIK, Unemployment